Análise da referência e contrarreferência entre atenção primária e secundária em saúde bucal em uma microrregião de Minas Gerais : estudo exploratório - Freitas, Érica Michelle Gonçalves De Lima (2023)
The implementation of secondary care is currently a major challenge for achieving comprehensiveness in the Unified Health System (SUS). The difficulties encountered in this path are definitely the obstacles to comprehensiveness. The objective of this study was to know the profile of referral and counter-referral between primary and secondary oral health care in the Alfenas/Machado health micro-region, in Minas Gerais, according to the perspective of dentists working in primary care units. An exploratory, descriptive study was carried out, with a quali-quantitative approach, using a semi-structured questionnaire, as a data collection instrument, written in Google Forms and sent via e-mail to the 80 dentists inserted in the attendance at the primary oral health care in the 16 municipalities belonging to the micro-region of interest. The TCLE was sent in the same e-mail, in order to clarify the voluntary research. Three contact attempts were made for each professional. The professional who did not respond to the request was excluded from the study. After collection, the primary data of this research were recorded in Microsoft Excel® 2010 and Epiinfo 7 spreadsheets. Descriptive statistics, frequency distributions were calculated and tabular and graphical representations were presented. Chi-square independence tests (5% significance) were applied to identify possible associations between variables. All tests, analyzes and graphics were performed in the R software version 4.2.1 (R CORE TEAM, 2022), through the RStudio program version 2022.02.3+492 (R STUDIO TEAM, 2022). As a result, reference to secondary care was found in 95% of the 16 municipalities evaluated. A large part of referrals are made to the two Universities of Dentistry in the center of the microregion (Alfenas-MG) (53%). There is only one Dental Specialty Center (CEO), in the city of Poço Fundo, which corresponds to only 21.6% of the referrals made in this micro-region. The most referred specialties were Endodontics (26.7%), Surgery (25%) and Periodontics (22.8%). Most professionals who do not refer users to specialized care advise users to seek private care (61.5%). Regarding the number of referrals, 36.7% of professionals made twenty or more referrals, 26.7% made 10 to 20 referrals, 23.3% referred 5 to 10 patients. The waiting time for assistance in specialized care ranged from 0 to more than 2 months, with a mode of 15 days to one month (33.3%). As for the patient's return to the unit of origin, after specialized care, most dentists (71.2%) stated that this return occurs. Finally, most dentists believe that the referral and counter-referral system of the microregion can be improved (85%). Significant relationships were found between the variables city and place of referral (p<0.003), city and number of referrals (p<0.001), city and waiting time (p<0.04) and between city and counter-referral (p<0 ,04). It is concluded that there is a reference for specialized care in the micro-region of interest, but professionals are not satisfied with the service. The main dental specialties are served, the number of referrals and the waiting time was known. It was verified the need for the existence of Specialty Centers that sufficiently serve the entire population.